Temporary Modifications To Access Limits Under The Large Natural Disaster Window Of The Rapid Credit Facility And Of The Rapid Financing Instrument. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2021)
To help support members faced with the COVID-19 pandemic, the Fund temporarily increased certain access limits to its emergency financing (EF) instruments, id est, Rapid Credit Facility (RCF) and Rapid Financing Instrument (RFI). While this expanded support has been critical to help countries manage the pandemic, the increase in access limits was not applied to the Large Natural Disasters (LND) windows within the EF toolkit, reducing the flexibility to respond to such LNDs. This paper proposes to temporarily increase by 50 percent of quota the annual access limit (AAL) and cumulative access limit (CAL) under the LND windows of the RCF and RFI. The changes to the 'LND windows' would be in effect through end-December 2021, in line with the other temporary changes of access limits under EF instruments. The case for further extensions to all the temporarily increased EF AALs and CALs will be examined after the 2021 Annual Meetings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Global Warming; Monetary Policy; Natural Disasters and Their Management; Political Economy